Experimental investigation of in-plane ultimate bearing capacity of parabolic high strength concrete-filled-steel-tubular arch. (February 2023) - Zhang, Yixiao; Liu, Airong; Huang, Yonghui; Yang, Jie; Fu, Jiyang; Yu, Yuguo; Zeng, Xinbing
Abstract: With the emergence of high-performance materials and the demand for light-weight long-span structures, high-strength concrete-filled-steel-tubular(HS-CFST)structures become increasingly popular. However, relevant research on HS-CFST arch remains scarce, and there is no systematic understanding on its mechanical characteristics. In this study, the in-plane ultimate bearing capacity of parabolic HS-CFST arch with fixed ends under vertical five-point-symmetrical-concentrated-loads along the span was studied experimentally. In total, 15 parabolic arch specimens consisting of different strength of steel tubes and core concretes were designed and tested. The mechanical responses of the arch specimens, including ultimate bearing capacity, failure modes, ductility coefficients, and confinement effects were analyzed. It is found that the ultimate bearing capacity, confinement effect and ductility of a HS-CFST arch are closely related to the strength of steel and core concrete. In addition, finite element models were established to predict the bearing capacity of the HS-CFST arch specimens, where the good agreements showcase the practical usefulness of the proposed HS-CFST arch. Highlights: The in-plane ultimate bearing capacity of parabolic high strength concrete-filled-steel-tubular arch was investigated. 15 parabolic arch specimens consisting of different strength of steel tubes and core concretes were designed and tested. The ultimate bearing capacity, failure modes, ductility coefficients, and confinement effects were analyzed. The experiment results were compared with the finite element analysis results.